E-mental health in child psychiatry during COVID-19: an initial attitudinal study. (October 2021) - Eapen, Valsamma; Dadich, Ann; Balachandran, Srilaxmi; Dani, Anitha; Howari, Rasha; Sequeria, Anupama Zeena; Singer, Joel D
Objective: COVID-19 propelled e-mental health within the Australian health system. It is important to learn from this to inform mental healthcare during future crises. Method: A lexical analysis was conducted of clinician reflections during COVID-19 as they delivered psychiatry services to children and families in New South Wales ( n = 6) and transitioned to e-mental health. Results: E-mental health can extend the reach of, and access to psychiatry services, particularly for individuals disadvantaged by inequity. Yet e-mental health can be problematic. It is partly contingent on technological prowess, equipment, internet access as well as space and privacy. Relatedly, e-mental health can hinder clinician capacity to conduct examinations, monitor child development as well as assess risk and the need for child protection. Conclusions: Given the benefits and limitations of e-mental health, a model that supports face-to-face mental healthcare and e-mental health may be of value. This model would require practical, yet flexible policies and protocols that protect the privacy of children and families, safeguard them from harm, and respect the needs and preferences of children, families and clinicians.